Approach to cryptographic key generation from fingerprint biometrics. (2015) - Barman, Subhas; Samanta, Debasis; Chattopadhyay, Samiran
In crypto-biometric system (CBS), biometric is combined with cryptography. In CBS, either accessing a cryptographic key is controlled with biometric or the key is generated from biometric features. This work is related to the latter approach in CBS. In such a system, protecting the privacy of the biometric data is an important concern. Further, there is a need to generate different cryptographic keys from the same biometric template of a user. Cancellable transformation of biometric data prior to the key generation is known as a solution. In this paper, we propose an approach to generate cryptographic key from cancellable fingerprint templates (CT ) of sender and receiver to ensure the privacy of the fingerprints and at the same time, it produces revocable key for the application of symmetric cryptography. The between-person variability of CT s guarantees the randomness which ensures that impostor users are not able to generate a genuine CT to break the cryptographic key.